Restruktur Kurikulum SMK Berbasis Pendidikan Agama Islam - Achmad Maulidi; Ali Tohir; Habibi Habibi; Muru'atul Afifah (Universitas Al-Amien Prenduan, 2020)
This research was conducted based on the phenomenon of vocational high schools located in rural areas and then adjustments were made to the curriculum which were oriented towards Islamic religious education. So this study aims to find out the background of the curriculum adjustment and how it is developed. This research is a qualitative case study type of data collection using observation interviews and documentation methods. The results of this study are that these adjustments occur due to geographical factors in rural areas that are still thick with customs that prioritize ethics both between humans and with their God. The adjustments and development are carried out by increasing the time and weight of the material, of course, with educators who are competent in this field.